Selection of assessment methods for evaluating banana weevil damage on highland cooking banana - Gold, Cliford S.; Ragama, P.E.; Coe, R.; Rukazambuga, N. (2004)
The banana weevil Cosmopolites sordidus (Germar) is an important pest on bananas and plantains (Musa spp.). Population build-up is slow and weevil problems become increasingly important in successive crop cycles (ratoons). Yield loss results from plant loss (death, snapping, toppling), mat disappearance (failure to sucker) and reduced bunch size. Damage assessment requires destructive sampling and is most often done on the corm periphery or corm cross sections of recently harvested plants. A wide range of damage assessment methods exist and there are no agreed upon assessment protocols. In this context, it is critical to know what types of damage best reflect weevil pest status through their relationships with yield loss. Multiple damage assessment parameters were employed in two long duration yield loss trials (cv Atwalira, Musa spp. AAA-EA) and a cultivar screening trial in Uganda. Parameters included two estimates of peripheral damage on pared corms and estimates of damage to the central cylinder and cortex (plus a derived total damage score) observed in cross sections. In the first two trials, estimated yield losses to banana weevil exceeded 40% in latter cycles. Damage to the central cylinder had a greater effect on plant size and yield loss than damage to the cortex or corm periphery. In some cases, a combined assessment of damage to the central cylinder and cortex showed a better relationship with yield loss than an assessment of the central cylinder alone. Regression (linear and logistic) and correlation analyses showed weak to modest relationships between damage to the corm periphery and damage to the central cylinder. Thus, damage to the corm periphery (less labour intensive to assess) is not a strong predictor of the more important damage to the central cylinder. Therefore, banana weevil damage assessment should be made for the central cylinder and cortex.